Transcriptome Signatures in Pseudomonas simiae WCS417 Shed Light on Role of Root-Secreted Coumarins in Arabidopsis-Mutualist Communication - Yu, Ke; Stringlis, Ioannis A; van Bentum, Sietske; de Jonge, Ronnie; Snoek, Basten L; Pieterse, Corné M J; Bakker, Peter A H M; Berendsen, Roeland L (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Pseudomonas simiae WCS417 is a root-colonizing bacterium with well-established plant-beneficial effects. Upon colonization of Arabidopsis roots, WCS417 evades local root immune responses while triggering an induced systemic resistance (ISR) in the leaves. The early onset of ISR in roots shows similarities with the iron deficiency response, as both responses are associated with the production and secretion of coumarins. Coumarins can mobilize iron from the soil environment and have a selective antimicrobial activity that impacts microbiome assembly in the rhizosphere. Being highly coumarin-tolerant, WCS417 induces the secretion of these phenolic compounds, likely to improve its own niche establishment, while providing growth and immunity benefits for the host in return. To investigate the possible signaling function of coumarins in the mutualistic Arabidopsis-WCS417 interaction, we analyzed the transcriptome of WCS417 growing in root exudates of coumarin-producing Arabidopsis Col-0 and the coumarin-biosynthesis mutant f6'h1. We found that coumarins in F6'H1-dependent root exudates significantly affected the expression of 439 bacterial genes (8% of the bacterial genome). Of those, genes with functions related to transport and metabolism of carbohydrates, amino acids, and nucleotides were induced, whereas genes with functions related to cell motility, the bacterial mobilome, and energy production and conversion were repressed. Strikingly, most genes related to flagellar biosynthesis were down-regulated by F6'H1-dependent root exudates and we found that application of selected coumarins reduces bacterial motility. These findings suggest that coumarins' function in the rhizosphere as semiochemicals in the communication between the roots and WCS417. Collectively, our results provide important novel leads for future functional analysis of molecular processes in the establishment of plant-mutualist interactions.
Keywords: Coumarins; Induced systemic resistance; Iron deficiency; Plant-beneficial rhizobacteria; Tran-scriptomics; Microbiology; Microbiology (medical); Virology